2021
DOI: 10.1091/mbc.e20-08-0525-t
|View full text |Cite
|
Sign up to set email alerts
|

Mps1 promotes poleward chromosome movements in meiotic prometaphase

Abstract: In prophase of meiosis I, homologous chromosomes pair and become connected by crossovers. Chiasmata, the connections formed by crossovers, enable the chromosome pair, called a bivalent, to attach as a single unit to the spindle. When the meiotic spindle forms in prometaphase, most bivalents are associated with one spindle pole and then go through a series of oscillations on the spindle, attaching to and detaching from microtubules until the partners of the bivalent become bioriented - attached to microtubules … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 75 publications
0
2
0
Order By: Relevance
“…In fission yeast, the spindle checkpoint proteins Bub1, Bub3, and Mad1 have been implicated in promoting these movements 49,51 Our data are consistent with the model that Mps1 supports the direct and/or indirect routes of achieving biorientation. Prior work has shown that Mps1 promotes movements of meiotic chromosomes across the spindle that appear to be similar to the direct route -mediated by microtubules that reach from one pole across the spindle to attach to a kinetochore on the other half of the spindle -and moving the chromosome towards the spindle midzone 32,52 Because the microtubule has to stretch across the spindle, this process would presumably be more efficient in cells with short spindles. However, on longer spindles like those found in polyploid cells with prolonged prometaphases, the direct route may be limited, and chromosomes may rely more heavily on an indirect route.…”
Section: Discussionmentioning
confidence: 96%
“…In fission yeast, the spindle checkpoint proteins Bub1, Bub3, and Mad1 have been implicated in promoting these movements 49,51 Our data are consistent with the model that Mps1 supports the direct and/or indirect routes of achieving biorientation. Prior work has shown that Mps1 promotes movements of meiotic chromosomes across the spindle that appear to be similar to the direct route -mediated by microtubules that reach from one pole across the spindle to attach to a kinetochore on the other half of the spindle -and moving the chromosome towards the spindle midzone 32,52 Because the microtubule has to stretch across the spindle, this process would presumably be more efficient in cells with short spindles. However, on longer spindles like those found in polyploid cells with prolonged prometaphases, the direct route may be limited, and chromosomes may rely more heavily on an indirect route.…”
Section: Discussionmentioning
confidence: 96%
“…7b ) ( Marston 2014 ). As in mitotic cells, proper orientation is continuously probed by the formation of kinetochore-microtubules attachments and their subsequent severing induced by Ipl1 (Aurora B) kinase ( Monje-Casas et al 2007 ; Meyer et al 2013 , 2021 ; Cairo et al 2020 ). When bipolar attachment is achieved, spindle forces are resisted by crossovers together with sister chromatid cohesion along chromosome arms that link recombinant homologous chromosomes ( Buonomo et al 2000 ).…”
Section: Metaphase Imentioning
confidence: 99%